Effects of atropine on choroidal thickness in myopic children: a meta-analysis - Yang, Yaqi; Wei, Lijuan; Wang, Bo; Zheng, Wei (Frontiers in Pharmacology, 2024)
Atropine is an effective medicine for myopia prevention and control. This metaanalysis was conducted to investigate the effects of atropine on choroidal thickness (ChT) in children with myopia.Between its inception and June 1, 2023, Medline, Embase, and Web of Science were all searched, and only English literature was included. The choroidal thickness was the primary study outcome. Axial length, standardized equivalent refraction were examined as secondary outcomes. STATA 12.0 was used for data extraction and analysis.A total of 307 eyes were involved in this study to evaluate the effect of atropine on ChT, axial length (AL) and standardized equivalent refraction (SER) in myopic children. Choroidal thickening was significantly higher in the atropine group than in the control group at 1 month, whereas it was significantly higher in the atropine group than in the control group at months 6, 12 and at final follow-up (WMD, 11.52mm, 95% CI, -3.26 to 26.31, P = 0.127), the differences were not statistically significant. Limited evidence suggests that 0.01% atropine causes choroidal thickening in myopic children at 1 month of treatment. In the short term, choroidal thickness may be a predictor of the effectiveness of atropine in controlling myopia in children. 0.01% atropine is effective in controlling myopic progression in terms of SER and AL.